Impact of row planting teff technology adoption on the income of smallholder farmers: The case of Hidabu Abote District, North Shoa Zone of Oromia Region, Ethiopia - Fekadu Adamu Negussie (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
In Ethiopia, improved agricultural technologies, like row planting are promoted in the recent times in order to address low agricultural productivity. However, despite such production enhancing technologies, utilization of such technologies remained low in Ethiopia. This study is focusedon the impact of row planting teff technology adoption on the income of smallholder farmer in the context of Hidabu Abote District, North Shoa zone. The study uses cross-sectional data that were collected from 181 randomly selected smallholder farmers. The data were analyzed using descriptive, inferential statistics,and econometrics models. From the descriptive statistics, it was found that out of thirteen explanatory variables seven of them were a significant difference among the groups. Results of the probit model revealed that, distance to central market, extension contact,off/non-farm income,farm size,household size, access to mass media,and access to credit affected the farmer's adoption decision of the row planting of teff significantly. The finding of the propensity score matching analysis revealed that the average teff income per hectare of adopter is greater than that of non-adopter. Therefore, the findings of the study safely recommended that those significant factors adoption decision of the row planting of teff by any development intervention and policy makers, should be considered in setting their policies and strategies to speed up the use of row planting of teff.